Controls of reservoir quality for submarine fan of F4 Formation in the Z oilfield, Illizi Basin, Algeria - Changhai Li; Weiqiang Li; Hui min Ye; Qiang Zhu; Xuejun Shan; Hongping Wang; Shengli Wang; Ziyu Zhang; Xianjie Zhou; Zixin Xue; Rongtu Ma (Scientific Reports)
Abstract Subaqueous fan reservoirs have emerged as a pivotal focus in recent deep-water oil and gas exploration. In the Illizi Basin of Algeria, a series of submarine fan reservoirs are developed within the Devonian F4 Formation of the Z oilfield. Understanding the genesis of high-quality reservoirs (defined as those with porosity exceeding 25% and permeability greater than 1000 mD) is crucial for pinpointing high-productivity wells in deep-water submarine fan settings. By integrating core data, thin-section analysis, grain-size data, logging data, and petrophysical property data, this study systematically classifies the depositional environments in the study area, constructs a sedimentary-logging identification template, maps the spatial distribution of lithofacies associations, identifies diagenetic types and evolution sequences, assesses reservoir quality, uncovers the origin of high-quality reservoirs and formulates a genetic model for high-quality reservoirs. The findings show that the study area encompasses 12 rock lithofacies types and 6 lithofacies associations, with braided river channels and interchannel facies being the predominant facies. Four diagenetic processes—compaction, cementation, dissolution, and fracturing—have been identified. Compaction and cementation tend to decrease porosity and permeability, while dissolution and fracturing enhance these properties. Four diagenetic evolution sequences, namely calcite cementation, dolomite cementation, muddy cementation, and quartz cementation, are recognized. Reservoirs associated with calcite and dolomite cementation sequences generally exhibit superior properties due to more strongly developed dissolution, whereas those related to muddy and quartz cementation sequences are of poor quality. Notably, high-quality reservoirs such as LF2, LF7, and LF9 developed in braided river channel microfacies have undergone calcite cementation. These findings verify the critical interplay between depositional facies and diagenetic processes in determining reservoir quality, providing valuable insights for future exploration and production strategies in similar geological settings.